Determination of possible route for invaders at Kota Putra, Padang Terap using [UAV] image / Mohamad Arham Mahasan - Mahasan, Mohamad Arham (2019)
In order to uphold the sovereignty of the state, the defence system and the immunity of state borders rather than easily encroached upon by intruders must be well maintained. The Lahad Datu intrusion gave a surprise to Malaysia as it involved nonstate actors from foreign countries. The question arises in questioning the fragility of the country's defence structure and the failure of the Malaysian Maritime Enforcement Agency (APMM) for delays in detecting the entry of the armed forces to enable them to capture Kampung Tanduo and Felda Sahabat 17 in Sabah. Therefore, this study was established through the "Persatuan Sejarah Malaysia Cawangan Kedah Darul Aman" to discuss the direction and sovereignty of the Kedah State borders from being infringed. This study begins with looking at the history of Padang Terap area and the study on the surface of the earth in the area using mapping from the UAV in line with the purpose of this study, to study the capabilities of UAV in providing good data in conjunction with the available data from JUPEM which uses conventional photogrammetry method. Furthermore, the three objectives that have been achieved from this study have explained the capabilities and capabilities of UAV in providing data that meets the desired requirements. With this, the assessment of tracing potential routes for intruders using UAV is seen to be more economically in terms of cost and time. Smaller consumer demands and time for faster aerial photo processing cause more relevant UAVs to be used today than conventional photogrammetry methods.